General ward nurses’ knowledge, attitude and skills on risk of deterioration assessment among patients: a comparison between hospitals in the East Coast Malaysia- a proposal - Mohamad , Shatirah; Mohamad Ali, Noorazizah; Mohamed Ludin, Salizar (2014)
Introduction: Research has shown that patients in general hospital wards often show early signs and symptoms, when their condition is getting worse. It is thought that if hospital staffs namely the nurses could identify and manage these patients earlier then there would be less critically ill patients, deaths or ICU admissions. Problem Statement: The challenge of recognizing the ward-based patient at risk of deterioration is discussed frequently within the literature. As their role enables them to be in constant contact with patients, nurses are in a prime position to identify problems at an early stage with the use of systematic patient assessment. Appropriate treatment can be initiated quickly, potentially saving the patient's life (Allen, 2004). Failure to recognize or act on deterioration of general ward patients has resulted in the implementation of early warning scoring systems and critical care outreach teams (Ordell, Victor & Oliver 2009). However, to date, there is no formal policy or information on Critical Care outreach services in Malaysian hospital and ward nurses’ knowledge on assessing the risk of deterioration on critically ill patients also not well understood. Objective: This study is to examine nurses’ knowledge, attitude and perception on the risk of deterioration among critically ill patients in general wards, determine the assessment required used to detect deterioration of condition, identify their nursing intervention the have provided should there is sign/symptom of risk or deterioration, distinguish the needs of Critical care services required in the general ward to assist them and understand the nurses’ experience in caring for critically ill patients’ with deteriorated condition.Methdology: This is a mixed method study whereby self- administered survey, document analysis and individual interviews will be used to collect the data from nurses in Medical and Surgical wards at tertiary hospital in each state, in East Coast Malaysia. SPSS will be used for for descriptive and inferential statistical analysis, and Nvivo 10 for qualitative analysis. Expected Outcome: Variety of data will be obtained and will complement each other. Significant of the study: Exploration of general ward nurses’ knowledge, attitude and perception on the ’risk of deterioration’ among critically ill patients will provide information on the need of ICU outreach service in Malaysian hospital. Through this research, evaluation can be made on the nurses readiness and ability to assess critically ill patients’ condition in prevention detecting the sign and symptom of deterioration and prevention of ICU admission or death and to ensure the quality of critically ill patients discharge from ICU.